LESSON STUDY FOR LEARNING COMMUNITY IN TEACHING ENGLISH FOR PUBLIC SPEAKING - Satriani, Intan; Yugafiati, Rasi; Suryani, Lilis (ELTICS : Journal of English Language Teaching and English Linguistics, 2017)
Abstract This paper proposes lesson study as a model for improving pedagogical skill especially in teaching English for Public Speaking. The lesson study has three steps. Those are plan, do, and see. In a small group, several lecturers design the material and the methods. One lecturer is being a class lecturer of English for Public Speaking, the rest of them are being observers. The class lecturer explains about the lesson plan. The rest of them give comment and suggestion. The class lecturer apply the lesson plan which has revised to the students. The observers observe studentsâ€™ responds. After the class has finished, the class lecturer and the observers discuss their progress. They evaluate the class activity and make the next lesson plan. It shows that lesson study help the students to increase their understanding of English for Public Speaking. The lesson plan also give insight to class lecturer and the observers. Â  Keywords: lesson study, public speaking, teaching English